La declaración de derechos en los nuevos Estatutos de Autonomía - Canosa Usera, Raúl (Teoría y Realidad Constitucional, 2007)
The incorporation of a Bill of Rights in each new Statute of Autonomy, recently approved, suppouses a radical novelty in Spain. In a way, «federalizes» the Spanish System of Rights, far away from the Unitary States. From now on will co-exist two levels of Bill of Rights: Constitucional and Autonomic. It does not implies specific competences to the Autonomic Communities, but will do require a big effort from all jurists to clear up the many doubts of this new situation; are these true rights?; how can we protect them?